Особенности стримерной короны со стержневых молниеприемников - Чернухин, Александр Юрьевич; Князев, Владимир Владимирович (НТУ "ХПИ", 2015)
В статье представлены результаты экспериментальных исследований стримерной короны со стержневых молниеприемников, в предгрозовой период. На основании статистической обработки результатов установлена эмпирическая зависимость количества одиночных стримеров в коронном разряде от напряженности электрического поля, в котором находится молниеприемник. Доказано существенное отличие в характере зависимости для стержня квадратного сечения с плоской вершиной и стержня кругового сечения с заостренной вершиной.

In the article the results of experimental researches of streamer crown are presented from cored air terminals in a pre thunderstorm period. On the basis of statistical treatment of results empiric dependence of amount of single streamers is set in a corona digit from tension of electric-field there is air terminal in that. A substantial difference is well-proven in character of dependence for the bar of square section flat-top and bar of circular section with a sharp top. It is set that corona digit from a sharp bar in the range of tension of electric-field from 6 kV/m to 10 kV/a m ceases. The following frequency arrives at 6 kG at the height of tension of field Е to 30 kV/m. It is set that frequency of the following of streamers for the case of bar of square section has the determined character: with the height of tension of Е-field the following frequency droningly increases with a coefficient near to 0.25 s-1 V-1 m. Value of standard deviation at other equal terms for the case of square bar on an order less than, what for the case of sharp bar.
A features of streamer crown are from cored air terminals
Keywords: электрофизические процессы; предгрозовые условия; напряженность электрического поля; частота следования стримеров; pre thunderstorm period; streamer crown; number of single streamers; tension of electric-field; cored air terminal